Preoperative Interventions for Alcohol and Other Recreational Substance Use: A Systematic Review and Meta-Analysis - Budworth, Luke; Prestwich, Andrew; Lawton, Rebecca; Kotzé, Alwyn; Kellar, Ian (Frontiers in Psychology, 2019)
Abstract Background. Preoperative alcohol and other recreational substance (ORSU) use may catalyse perioperative complications. Accordingly, interventions aiming to reduce preoperative substance use are warranted. Methods. Studies recruiting hazardous/dependent alcohol, or other recreational substance users, were identified from: Cochrane Library; MEDLINE; PSYCINFO; EMBASE; and CINAHL. Interventions to reduce alcohol and/or ORSU in elective surgery patients were included. In both narrative summaries of results and random effects meta-analyses, effects of interventions on perioperative alcohol/ORSU, perioperative complications, mortality and length of stay were assessed. Primary Results Nine studies (n = 903) were included. Seven used behavioural interventions only, two provided disulfiram in addition. Pooled analyses found small effects on alcohol use (d: 0.34; 0.05-0.64), though two trials using disulfiram (0.71; 0.36-1.07) were superior to two using behavioural interventions (0.45; -0.49-1.39). No significant pooled effects were found for perioperative complications, length of hospital stay or mortality in studies solely targeting alcohol/ISU. Too few interventions targeting ORSU (k =1) were located to form conclusions regarding their efficacy. Studies were generally at high risk-of-bias and heterogeneous. Conclusions Preoperative interventions were beneficial in reducing substance use in some instances, but more high-quality studies targeting alcohol/ORSU specifically are needed. The literature to date does not suggest that such interventions can reduce postoperative morbidity, length of hospital stay or mortality. Limitations in the literature are outlined and recommendations for future studies are suggested.